MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI MODEL PROBLEM BASED LEARNING - irda, irdawati (Global Journal Teaching Professional, 2023)
Received; Revised: Accepted; Published, This research is a quasi-experimental or quasi-experimental study that aims to determine the effect of using learning videos on The problem behind this research is the low learning outcomes of students in class III SD Inpres Taruttu Campaga, Kecamatan Tompobulu, Kabupaten Bantaeng. This study aims to describe the application of the Problem Based Learning learning model to improve student learning outcomes. The approach used is a qualitative approach and a type of classroom action research (PTK), which consists of 2 cycles, starting with the stages of activities including planning, implementing, observing, and reflecting. The focus of the research was students of class III SD Inpres Taruttu Campaga, Kecamatan Tompobulu, Kabupaten Bantaeng in the even semester of the 2022/2023 academic year, a total of 14 students. Data collection uses the format of observation, tests, and documentation. The data analysis used is qualitative. The results showed that during the implementation of cycles I and II, the research results in cycle I were in the sufficient category, and there was an increase in cycle II which was in the good category. The conclusion of this study is that applying the Problem Based Learning model can improve the learning process and learning outcomes of students in class III SD Inpres Taruttu Campaga, Kecamatan Tompobulu, Kabupaten Bantaeng Permasalahan yang melatar belakangi penelitian ini adalah rendahnya hasil belajar peserta didik di kelas III SD Inpres Taruttu Campaga Kecamatan Tompobulu Kabupaten Bantaeng. Penelitian ini bertujuan untuk mendeskripsikn penerapan model pembelajaran problem based learning untuk meningkatkan hasil belajar peserta didik. Pendekatan yang digunakan adalah pendekatan kualitatif dan jenis penelitian tindakan kelas (PTK) yang terdiri dari 2 siklus, diawali dengan tahapan kegiatan meliputi perencanaan, pelaksanaan, observasi, dan refleksi. Fokus penelitian adalah peserta didik kelas III SD Inpres Taruttu Campaga Kecamatan Tompobulu Kabupaten Bantaeng pada semester genap tahun ajaran 2022/2023 yang berjumlah 14 orang peserta didik. Pengumpulan data menggunakan format observasi, tes, dan dokumentasi. Analisis data yang digunakan adalah kualitatif. Hasil penelitian menunjukkan selama pelaksanaan siklus I dan II diperoleh hasil penelitian pada siklus I berada pada kategori cukup, dan terjadi peningkatan pada siklus II yang berada pada kategori baik. Kesimpulan penelitian ini yatu dengan menerapkan model problem based learning dapat meningkatkan proses pembelajaran dan hasi belajar peserta didik di kelas III SD Inpres Taruttu Campaga Kecamatan Tompobulu Kabupaten Bantaeng.